Acibenzolar-S-Methyl Reprograms Apple Transcriptome Toward Resistance to Rosy Apple Aphid - Warneys, Romain; Gaucher, Matthieu; Robert, Philippe; Aligon, Sophie; Anton, Sylvia; Aubourg, Sébastien; Barthes, Nicolas; Braud, Ferréol; Cournol, Raphaël; Gadenne, Christophe; Heintz, Christelle; Brisset, Marie-Noëlle; et al. (Frontiers in Plant Science, 2018)
Acibenzolar-S-methyl (ASM) is a chemical compound, which is able to induce resistance in several model and non-model plants, but the end-players of this induced defense remain ill-defined. Here we test the hypothesis that treatment with ASM can protect apple (Malus x domestica) against the rosy apple aphid (Dysaphis plantaginea) and investigate the defense molecules potentially involved in resistance. We measured aphid life traits and performed behavioral assays to study the effect of ASM on plant resistance against the aphid, and then combined transcriptomic, bioinformatics, metabolic and biochemical analyses to identify the plant compounds involved in resistance. Plants treated with ASM negatively affected several life traits of the aphid and modified its feeding and host seeking behaviors. ASM treatment elicited up-regulation of terpene synthase genes in apple and led to the emission of (E,E)-α-farnesene, a sesquiterpene that was repellent to the aphid. Several genes encoding amaranthin-like lectins were also strongly up-regulated upon treatment and the corresponding proteins accumulated in leaves, petiols and stems. Our results link the production of specific apple proteins and metabolites to the antibiosis and antixenosis effects observed against Dysaphis plantaginea, providing insight into the mechanisms underlying ASM-induced herbivore resistance.